Book museum of Šilutė Frydrichas Bajoraitis publiclibrary (1990-2001) - Užpelkienė, Dalia (Knygotyra, 2003)
Book museum was opened on the 29 of September 1990 when 45th anniversary of Šilutė central library (now the F. Bajoraitis public library) was celebrated. Idea of foundation belongs to the library collective and professor of Vilnius University, researcher of Minor Lithuania book Domas Kaunas. It is a public book museum open and accessible to all users of library service. Museum functions at bibliographic-methodical department. The main types of activity: to accumulate, preserve and publish cultural historical heritage material of Pamarys region, valuable information about monuments of book history, famous people of book culture, places connected with their life and activity, present achievements of book publishing of Pamarys land.There are 2962 copies of old and valuable to heritage of Pamarys land publications concentrated in the museum, about 1200 manuscripts and copies of documents connected with important facts of book culture, 19 personal book collections, presented by emigrants from Pamarys who live now abroad and by individual inhabitants of Šilutė. Now museum has 135 copies of dedicated and autographed books, this collection has begun complete in 1985.Besides books, manuscripts, photo museum preserves over 800 original art works of Lithuanian and foreign artists, among them – 455 ex-librises, 283 souvenirs, 6 musical instruments, 1 sculpture. All displays of museum in one or other way are connected with book, its surroundings and book authors.From 1993 series of exhibitions "From funds of book museum" is arranging. Together with Šilutė museum exhibition "Old book of Šilutė" (1998) was organized, photo documentary exposition "Vydūnas (Vilhelmas Storosta)" was exhibited in historical museum in Tilžė (1999), "Šilutė in written sources" in Nida (2002), "Professor Levas Vladimirovas and Šilutė" (2001 in Vilnius University), i.e. in popularization of book museum funds international scientific conference "Martynas Mažvydas – beginning of beginnings" (2002) was organized together with H. Zudermanas literary regional club of Šilutė, days of Šilutė book in Academy of Sciences of Lithuanian Republic (2001), i.e.Memorial plaques to Šilutė bibliophiles Sekunos and Karlas Sekuna were unveiled on initiative of librarians in perpetuation of memory of famous Pamarys land bibliophiles and printers (1997). In 2001 public library specialists used published and not published material from book museum and with help of 104 authors prepared and published encyclopaedic dictionary "Šilutė land", it was exhibited in international book sale in Frankfurt (2001), in Tallinn (Estonia, 2002). Over 1000 visitors come to book museum in a year.
Keywords: -